INVESTIGASI MUSCULOSKELETAL DISORDERS (MSDs) PADA AKTIVITAS PANEN KELAPA DESA SIMPANG JAYA DUSUN BENTENG MAKMUR RT 12 RW 04 KECAMATAN BATANG TUAKA - Roberta Zulfhi Surya; Dede Nirawan; Khairul Ihwan (JUTI UNISI, 2018)
In this research will discuss about mosculoskeletal disorders (MSDs) investigation on coconut harvest activity Simpang Jaya Village Benteng Makmur Village RT 12 RW 04 Batang Tuaka District. From the recapitulation of the first questionnaire about the complaint when linking coconut fruit using eggrek showed that of 30 respondents (total sample) known level of MSDs on the type of complaints of pain / stiffness in the upper neck of the average of 30 respondents (total sample) of 2.2%. In recapitulation of calculation of second questionnaire data can be seen that from 30 respondents (total sample) known level of MSDs on activity collecting fruit keladaapada type of pain / stiffness in the upper neck of 2.2%. From the results of the recapitulation of the third questionnaire data shows that from 30 respondents (total sample) it is known that the MSDs level on the activity of bringing the orchids on the type of pain / stiff complaints in the upper neck of the average of 30 respondents (total sample) of 2.5%.